2013
DOI: 10.1016/j.watres.2013.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Activity of metazoa governs biofilm structure formation and enhances permeate flux during Gravity-Driven Membrane (GDM) filtration

Abstract: The impact of different feed waters in terms of eukaryotic populations and organic carbon content on the biofilm structure formation and permeate flux during Gravity-Driven Membrane (GDM) filtration was investigated in this study. GDM filtration was performed at ultra-low pressure (65 mbar) in dead-end mode without control of the biofilm formation. Different feed waters were tested (River water, pre-treated river water, lake water, and tap water) and varied with regard to their organic substrate content and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 15 publications
(1 reference statement)
2
69
0
Order By: Relevance
“…The detailed characteristics (Total organic carbon, assimilable organic carbon, etc.) of the Chriesbach creek water can be found in Derlon et al (2013). Water and room temperatures were controlled at 20 C. The Hydraulic Retention Time (HRT) was controlled to around 4 h in each water tank.…”
Section: Operating Conditionsmentioning
confidence: 99%
“…The detailed characteristics (Total organic carbon, assimilable organic carbon, etc.) of the Chriesbach creek water can be found in Derlon et al (2013). Water and room temperatures were controlled at 20 C. The Hydraulic Retention Time (HRT) was controlled to around 4 h in each water tank.…”
Section: Operating Conditionsmentioning
confidence: 99%
“…Although their grazing pressure on biofilm microphytobenthos is rather low (Majdi et al, 2012b, c;Mialet et al, 2013), their activity within the biofilm can affect oxygen turnover (Mathieu et al, 2007) and seemingly other key processes such as biofilm detachment and the release of secondary metabolites in the water column (Sabater et al, 2003;Gaudes et al, 2006). Recently, Derlon et al (2013) have shown that, in gravity-driven membrane filtration water depuration systems, the presence of nematodes and oligochaetes increases the heterogeneity and porosity of membrane-associated microbial biofilms, and consequently increases the efficacy of filtration process used to treat organically polluted waters. Riemann & Helmke (2002) report that locomotion of nematodes creates dense micro-burrows from agar plate matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al proved its potential for visualizing liquid flow patterns in spacer filled feed channels [16]. The effect of (natural) predation on the structure of the fouling layer in gravity driven membrane systems has been shown by Derlon et al [17]. In another study the compaction and detachment of the biofouling layer in a microfiltration unit was investigated [18].…”
mentioning
confidence: 99%